Sustaining higher productivity of rice through varietal intervention in water logged areas of Eastern India - Dwivedi, Sharad Kumar; Kumar, Santosh; Singh, S. S.; Shivani, Shivani (Indian Farming, 2015)
Selection of submergence tolerant cultivars and identification of morpho-physiological traits responsible for submergence tolerance is a greater achievement under submergence situation. Introgression of submergence tolerant gene Sub 1 in sensitive mega varieties Swarna, IR 64 and Sambha Mahsuri etc will improve and stabilize the productivity of rainfed lowland rice areas prone to flash as well asstagnant flooding. There is need to develop new Sub 1 mega varieties and effectively provide submergence tolerance without apparent effect on development, productivity and grain quality. These water proof rice cultivars will give us the solution of the hunger problem in India particularly in eastern region.